Patterns of Firm-Level Productivity in Ireland - Papa, Javier; Rehill, Luke; O'Connor, Brendan (The Economic and Social Review, 2021)
Although Ireland is a high productivity country, it has not been immune from the global productivity slowdown, with the pace of growth on a downward trend throughout the 2000s. To identify the determinants behind the aggregate productivity growth in Ireland we use a firm-level panel dataset from the CSO to study productivity patterns and trends distributed by percentile, sector, ownership, as well the efficiency of resource allocation. Our results show a widening of the productivity gap between the most and least productive firms, consistent with cross-country results from the OECD. Results also confirm that aggregate productivity statistics are heavily dominated by a small number of foreign owned firms, leaving Ireland’s productivity prone to firm-specific shocks, while also disguising the performance of domestic sectors and firms. Lastly, allocative efficiency, a key driver of productivity, does not appear particularly strong amongst domestic sectors of the economy.